Dampak Pandemi Covid-19 Terhadap Kondisi Sosial Ekonomi Keluarga Buruh di Dusun VII Desa Sampali Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Lopisa Laura (Universitas Muhammadiyah Sumatera Utara, 2022)
Sampali Village is one of the villages in the Percut Sei Tuan sub-district, Deli Serdang Regency, North Sumatra Province with a population of approximately 18,382 people. The area of Sampali village is 401 H, consisting of 25 hamlets whose settlements are industrial areas, development centers, elite housing and so on. On average, the local people of Sampali village make a living as private employees and traders or entrepreneurs. With the Covid-19 outbreak which has been designated by the government as a natural disaster, this is the reason for force majeure to terminate the employment relationship with the government. This greatly affects the socio-economic conditions of the workers' families in Hamlet VII, Sampali Village, Percut Sei Tuan District, especially with regard to meeting basic family needs such as food, clothing, food, shelter, education, and health. In addition, the role of the wife becomes a dual role because she participates in making a living. The existence of assistance from the government and business loans from banks is very helpful for families to overcome socio-economic problems.